Alexithymia, intolerance to uncertainty and mental health difficulties in adolescents with Type 1 diabetes mellitus - Merlo, EM; Tutino, R; Myles, LAM; Lia, MC; Minasi, D (BioMed Central, 2024)
Background: Type 1 Diabetes Mellitus (T1DM) represents a serious chronic condition affecting a wide number of people. Discussion of the physical issues associated with T1DM pervades the literature, however, there is less discussion of the psychological consequences. Mental health difficulties, alexithymia and uncertainty are present in this population, and known to be harmful for the onset, maintenance and worsening of T1DM. This study aimed to evaluate the presence of these phenomena in people with T1DM. Methods: 105 participants aged between 11 and 17 years old (M: 13.88; SD: 2.16) affected by T1DM were included in the sample. To assess the presence of mental health difficulties, SAFA scales (Depression, Anxiety and Somatic symptoms) were included in the protocol together with TAS-20 and IUS-12, which evaluate the presence and role of alexithymia and intolerance to uncertainty in the sample, respectively. Results: A concerning presence of anxiety, depression and somatic symptoms was found in the sample. Mental health difficulties appeared to be consistently present in the sample, often overcoming pathological thesholds. Alexithymia and uncertainty were also common, highlighting their role in T1DM. Conclusions: Active mental health difficulties together with high rates of alexithymia and intolerance to uncertainty were prevalent in the sample of adolescents with diabetes.